1992
DOI: 10.1111/j.1365-277x.1992.tb00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new questionnaire for assessing habitual intake of starch, non‐starch polysaccharides, sugars and alcohol

Abstract: A newly developed food frequency questionnaire designed to estimate habitual intake of non-starch polysaccharide (NSP), intrinsic and extrinsic sugars, starch and alcohol was compared with 4-d weighed records using the semi-automatic Petra system in 154 subjects, men aged 40-69 years and women aged 25-69 years. There was no statistical difference between the two methods for average intake of NSP (soluble and insoluble) intrinsic sugar and Vitamin C. Where a significant difference did occur, notably in extrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Mothers were asked about their current weekly frequency of consumption of 43 food groups and food items, and about daily consumption of a further eight basic foods. The foods chosen were based on those used by Yarnell et al 30 and modified in the light of a more recent weighed dietary survey 31. Additional questions asked about the types of certain foods used and about the ways in which food was prepared and eaten 32.…”
Section: Methodsmentioning
confidence: 99%
“…Mothers were asked about their current weekly frequency of consumption of 43 food groups and food items, and about daily consumption of a further eight basic foods. The foods chosen were based on those used by Yarnell et al 30 and modified in the light of a more recent weighed dietary survey 31. Additional questions asked about the types of certain foods used and about the ways in which food was prepared and eaten 32.…”
Section: Methodsmentioning
confidence: 99%
“…A study of middle-aged women in Cambridge found that a food frequency questionnaire misclassi®ed only 2±10% of individuals into opposite quartiles for nutrient intake when compared with the results of a 16-day weighed intake (Bingham et al, 1994). Food frequency questionnaires are also considerably less time-consuming for those administering the surveyÐin the study by Emmett et al, 1992 administration and assessment of the food-frequency questionnaire took up approximately 30 min of the dieticians time, as opposed to 3 h for a 4-day weighed intake. The similarity of the results we have obtained using a food frequency questionnaire to those of the Dietary and Nutritional Survey of British Adults which used a seven-day weighed intake support their validity as an assessment of diet.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in South West England (Emmett et al, 1992) assessing habitual intake of sugar, non-starch polysaccharide (NSP), starch, vitamin C and carotene using a food-frequency questionnaire and a four-day weighed intake, there was no signi®cant difference between the average calculated nutrient intakes for NSP, intrinsic sugar and starch, and the differences in the calculated intakes of the other nutrients did not exceed 12%. A study of middle-aged women in Cambridge found that a food frequency questionnaire misclassi®ed only 2±10% of individuals into opposite quartiles for nutrient intake when compared with the results of a 16-day weighed intake (Bingham et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Mothers were asked how often they were currently eating each type of food, and from this, nutrient intakes based on standard sized portions were estimated using the 5th edition of McCance and Widdowson's The Composition of Foods and its supplements. [26][27][28][29][30][31][32] A full description of the methods used is given elsewhere.…”
Section: Maternal Dietmentioning
confidence: 99%